The resilience potential of different refugee reception approaches taken during the 'refugee crisis' in Amsterdam. (November 2020) - Rast, Maria Charlotte; Younes, Younes; Smets, Peer; Ghorashi, Halleh
The so-called refugee crisis in 2015/2016 created opportunities for faith-based organizations, community initiatives, volunteers and refugees to get actively involved in refugee reception in Amsterdam. This study investigated the resilience potential of three refugee reception approaches that were taken during that transformative period: those of a semi-governmental organization (COA), a faith-based organization (The Salvation Army) and a community initiative ( Hoost ). Based on qualitative data, the article shows that the nexus of regulations and flexibility in crisis responses impacts the ability to employ multiple local resources and thus predetermines the capacity to adopt resilient solutions to refugee reception during crises. The authors plead for daring governmental efforts that acknowledge, connect and facilitate the innovative power of local communities, faith-based organizations, volunteers and refugees in the refugee reception process without further withdrawals of state responsibility for refugee reception. However, it is crucial that such innovative efforts integrate and learn from existing knowledge to prevent mistakes from being repeated.